A Critical Look at Shahnameh (1) Shahriyar Namvarnameh (Selected for the Shahnameh Course) - Jamileh Akhyani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Selection of excerpts from ancient texts and explanation of their difficulties in the form of academic excerpts for teaching in the field of Persian language and literature is one of the works that has increased in recent years. Accurately selecting parts of texts and explaining their difficulties can help students better understand ancient texts and of course, the preparation of such books requires a great deal of expertise and a great deal of care and patience. Shahnameh's book (1) Shahriyar Namvarnameh published by Samt Publications is the result of the attention of prominent Shahnameh scholar Sajjad Aydenlo who has provided a well-deserved book for students. Despite the many benefits of this book including selecting three stories from the Shahnameh instead of one, arranging the contents of the book in a decent volume for one semester, designing important topics related to Ferdowsi and Shahnameh based on the latest Shahnameh researches and..., there are some shortcomings in its compilation that have been addressed in the present article. These deficiencies include the shortcomings of choosing the verses for the excerpts of the stories, the failures to explain and explain the verses, and the shortcomings of the version used in the excerpts, and the lack of explanation about them. The author hopes that by revising these shortcomings, this valuable book will become more disciplined.